Peran Pola Asuh Orang Tua dalam Penanaman Kemandirian Anak Usia Dini di Kelurahan Kramat Kecamatan Nganjuk Kabupaten Nganjuk - Al Baqi; Silma Raizhannah Maulida (UIN Kiai Ageng Muhammad Besari, 2023)
Parenting patterns are all interactions carried out by parents to provide support to children, by changing behavior, mentality and values ​​that make a child an independent, confident person and have a high curiosity. The aim of this research is (1) to determine the profile of parenting patterns in Kramat Village, Nganjuk District, Nganjuk Regency (2) the factors that influence the independence of early childhood in Nganjuk District, Nganjuk District (3) the contribution of parental parenting patterns to the independence of young children. early in Kramat Village, Nganjuk District, Nganjuk Regency. This type of research uses qualitative research using case studies, and is descriptive in nature. The research was conducted in Kramat Village, Nganjuk District, Nganjuk Regency. The data collection techniques used were observation, direct interviews and documentation with subjects of four parents of four children aged 4-5 years. Data analysis which includes data reduction, data presentation and drawing conclusions. The data obtained is then carried out in a data analysis process which aims to draw conclusions from the research process. Based on the research results that have been obtained, there are three types of parenting patterns given by parents, namely democratic parenting, authoritarian parenting and permissive parenting in training the independence of children aged 4-5 years. In parenting patterns to train independence, there are factors that influence children's independence, namely environmental factors, parenting patterns and education. From these factors, there is a contribution from different parenting styles to children's independence, such as democratic parenting, children will become more independent individuals, authoritarian parenting will make children less confident or hesitant, and permissive parenting, children will tend to often ask for help. From this, children's independence can be seen from the child's physical, mental, creative and emotional aspects.